Single-session ERCP in patients with previous Roux-en-Y gastric bypass using percutaneous-assisted transprosthetic endoscopic therapy: a case series - Law, R.; Wong Kee Song, L. M.; Petersen, B. T.; Baron, T. H. (Endoscopy, 2013)
Endoscopic retrograde cholangiopancreatography (ERCP) remains technically challenging following Roux-en-Y gastric bypass (RYGB). Various techniques have been described to access the excluded stomach. We describe our experience using percutaneous-assisted transprosthetic endoscopic therapy (PATENT) to perform antegrade ERCP. Balloon enteroscopy was used to access the excluded stomach. Direct retrograde percutaneous endoscopic gastrostomy (RPEG) was performed and an esophageal self-expandable metal stent (SEMS) was deployed within the gastrostomy tract. A duodenoscope was advanced through the SEMS and antegrade ERCP was performed. Following ERCP, a gastrostomy tube was placed through the SEMS to maintain patency. Five patients underwent successful antegrade ERCP using PATENT. All patients had a diagnosis of sphincter of Oddi dysfunction. Biliary sphincterotomy was performed in all patients and liver enzymes normalized in four patients with preprocedural elevations. In conclusion, antegrade ERCP employing PATENT is feasible and can be performed during a single endoscopic session in patients with previous RYGB.